Chu's day at the beach - Gaiman, Neil (Harper, an imprint of HarperCollinsPublishers, 2015)
"Chu and his family are going to the beach. Chu is excited. He will get to play in the sand and wade in the water. But what will happen if Chu sneezes at the beach? And what will happen if he doesn't?"--Dust jacket flap.